(untitled) (Reflection and Critique Law Magazine, 2020)
With the impressive evolution of human rights in the past decade, the sacred idea of state sovereignty has been fully overcome, which can be evidenced by the growing membership of States to international judicial mechanisms, submitting themselfs to international jurisdiction and, in parallel, the progressive conditioning of domestic law by the international human rights standards. In this sense, it is proposed in this paper to carry out a review of the court decision on "the demand for college degree for the exercise of journalism" (RE 511,961 / 2009) in the light of the human and fundamental right to freedom of expression and under the prism of the theory of conventionality control of laws.